Biological Management of Banana Fusarium Wilt Caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 Using Antagonistic Fungal Isolate CSR-T-3 (Trichoderma reesei) - Damodaran, Thukkaram; Rajan, Shailendra; Muthukumar, Manoharan; Ram Gopal,; Yadav, Kavita; Kumar, Sandeep; Ahmad, Israr; Kumari, Nidhi; Mishra, Vinay K.; Jha, Sunil K. (Frontiers in Microbiology, 2020)
Fusarium wilt in banana is one of the most devastating diseases that pose a serious threat to the banana industry globally. With no effective control measures being available till date, biological control has been explored to restrict the spread and manage the outbreak. We studied the effective biological control potential of different Trichoderma spp. in the management of Fusarium oxysporum f. sp. cubense Tropical race 4 (Foc TR4). Expression of the defense related genes and metabolites in banana plants inoculated with Foc TR4 and treated with effective Trichoderma sp interactions were also studied. The in-vitro growth inhibition of Foc TR4 by Trichoderma reesei isolate CSR-T-3 was 85.19 % indicating the higher antagonistic potential than other Trichoderma isolates used in the study. Further, in in-vivo assays, the banana plants treated with the isolate CSR-T-3 T. reesei had a significant reduction in the disease severity index (0.75) and also had increased phenological indices with respect to Foc TR4 treated plants. Enhanced activity of defense enzymes such as β-1,3 glucanase, peroxidase, chitinase, polyphenol oxidase and phenyl alanine ammonia lyase with higher phenol contents were found in the Trichoderma isolate CSR-T-3 treated banana plants challenge inoculated with Foc TR4. Fusarium toxins such as fusaristatin A, fusarin C, chlamydosporal and beauveric acid were identified by LC-MS in Foc TR4 infected banana plants while high intensity production of antifungal compounds such as ß-caryophyllene, catechin-o-gallate, soyasapogenol rhamnosyl glucoronide, peptaibols, fenigycin, iturin C19, anthocyanin, and gallocatechin-o-gallate were detected in T. reesei isolate CSR-T-3 treated plants previously inoculated with Foc TR4. Gene expression analysis indicated upregulation of TrCBH1/TrCBH2, TrXYL1, TrEGL1, TrTMK1, TrTGA1 and TrVEL1 genes in CSR-T-3 treatment. LC-MS and gene expression analysis could ascertain the upregulation of genes involved in mycoparasitism and signal transduction pathway leading to secondary metabolite production under CSR-T-3 treatment. The plants in the field study showed reduced disease severity index (1.14) with high phenological growth and yield indices when treated with T. reesei isolate CSR-T-3 formulation. We report here an effective bio-control based management technological transformation from lab to the field for successful control of Fusarium wilt disease caused by Foc TR4 in banana.